Authentication of IoT in Smart City applications - Khalifa, Othman Omran; Bin Japar, Danial Fareez; Abdul Rahman, Farah Diyana; Nasir, Haidawati (IEEE, 2022)
The advancement of technology brings an extensive use of Internet of things (IoT) devices in our daily life. IoT primary used for data collection and provide real-time management information in the network paradigms such as Edge Computing and Fog Computing. However, assuring the reliability of data delivered via Edge Computing is a challenging task. Blockchain has been a technology that has gained traction in recent years. Using Blockchain with IoT allows Smart Cities (SC) applications to spread security information, which protects against Distributed Denial of Service (DDOS) attacks. IoT devices in a SC can have a lengthy life, increasing the possibility of security flaws caused by obsolete firmware. This paper will highlight the significance of the implementation considering the SC and demonstrate a testbed made up of Blockchain Ethereum and actual IoT devices. The effects of transmission time, memory, and CPU use on the sending also processing of these messages were demonstrated. The proposed Application Programming Interface (API) sign, identify, and validate the messages before collecting them for an IoT data management application.